Industrial relations in Japan - Chalmers, Norma J. (London, 1989)
The conventional picture of industry and industrial relations in Japan is of a number of very large firms providing extremely attractive working conditions for their happy and contented workforce. Norma Chalmers shows that there is in fact another, very different side to the picture, which occurs in the the peripheral sector. Here, conditions are often poor, wages very low and continuity of employment virtually non-existent. There are many small firms where the effectiveness of worker organisation and bargaining declines as the firm's size and proximity to the industrial centre decrease. Moreover, as Chalmers shows, the peripheral sector is very large, and the conventional picture of the model workforce should probably be confined to a few flagship companies. The book argues that the model nature of the large firms may stem in part from the fact that they are able to off-load problems onto smaller firms who produce the components necessary for the large firm sector at disadvantageous subcontract terms.